Potential Test of Acceptability, Elasticity, Nutritional Content and Cyanide Acid: Wet Noodles Cassava Leaves - Aswita Amir; Juwita Vera Lestari; Kristina Sriwahyuningsih; Ledya Tri Anggaeni; Rudy Hartono (Politeknik Kesehatan Makassar, 2021)
AbstractNoodles is one of the foods favored by the people of Indonesia and economical and practical, so it is necessary to processing alternatives that qualify nutritionally with the addition of fiber from cassava leaves. This study aims to find out the acceptableness, elasticity, iron content, protein, fiber and hydrogen cyanide. This type of research is an experiment that is the manufacture of noodles using the addition of cassava leaves (15%, 30% and 50%) then conducted an analysis of protein, iron, fiber using gravimetry, analysis of hydrogen cyanide levels using volumetri with tools - ingredients are scales, sieves, molds, measuring cups, filters, wheat flour, egg whites, garlic, cassava leaves and salt. The results of the research from the preferred hedonic aspect are a concentration of 15%. Noodles with cassava leaves concentration of 15% have the elasticity value closest to wet noodles without cassava leaves which is 3.3 cm with medium category, the highest iron content with cassava leaves concentration of 50% as much as 0.5 mg / 100 grams, the highest fiber content as much as 9.67 grams per 100 grams, the highest HCN content as much as 15.7 mg per 100 grams, the highest protein content of noodles with cassava leaves concentration of 15% obtained as much as 8,222 grams / 100 grams. In conclusion, preferred acceptableness and elasticity as well as the highest protein content with 15% cassava leaves, the highest iron, fiber and HCN levels with a concentration of 50%.